IoT Based Smart Exhaust Fan - Navindran A/L Alagari; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2021)
There is a lot of technology improvement in exhaust fan. The world is moving rapidly towards the automated or smart mechanism. Although there is a lot of system, but there is some drawbacks in exhaust fan which could operate on its own with human interface. Manual operate exhaust fan may not work efficiently in terms of human error and also high electric consumption. The real support for this problem is due to the inability of the user or humans to define the most appropriate temperature and air quality in a space. The user will have difficulty to sense temperature and air quality directly by their body. Besides that, humans tend to forget things, it will be difficulty for the user to turn ON and OFF the fan on right time. They will forget to turn ON or OFF the device or let the device turn ON without noticing or forget about it. This cost waste in power consumption and rises the electric bill because of inefficient performance from the device. In this project, an IoT based smart exhaust fan will be developed to control and monitor the exhaust fan automatically without human interface. This device able to sense the difference in temperature and air quality in space. If the sensor sense the level of the temperature and air quality exceeded more than required, a notification will be send to the device display and also any device which can access internet. Then the exhaust fan will turn ON and OFF automatically when the level is reduced below than critical level.